Safer opioid analgesics: targeting truncated Mu opioid receptor splice variants - Pan, Ying-Xian (Henry Stewart Talks, 2022)
Mu opioid receptor, Opioids, Morphine, Alternative splicing of OPRM1, Analgesia, 3’-iodobenzoyl-6beta-naltrexamide (IBNtxA), Lentivirus analgesia rescue